2020
DOI: 10.1155/2020/7610436
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Magnesium Intake and Leukocyte Telomere Attrition in Adults: The Regulatory Role of Serum Tumor Necrosis Factor α

Abstract: Objectives. In this study, we assessed the effects of dietary magnesium on leukocyte telomere length (LTL). Designs. The current cross-sectional analysis was based on data collected within a type 2 diabetes project. Settings. Dietary magnesium intake is associated with peripheral blood leukocyte telomere length (LTL). However, few epidemiological studies have evaluated the effects of magnesium on LTL in the clinical setting. Participants. This cross-sectional analysis included 467 participants (34.8% men). Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Zinc deficiency is thought to be responsible for poor wound healing (Medicine 2003). As for magnesium the content ranged from 9.19 ppm to 18.6 ppm was lower than 300 ppm recommended daily as confirm Yu et al 2020 [31], its deficiency contributes to the aging of the skin, which can lead to a skin healing disorder, as supported by Colboc and Meaume 2018 [32]. As for calcium, it is essential for the vascular phase of healing leading to hemostasis, coagulation and fibrosis as mentioned by Démarchez 2014 [33], calcium deficiency can be the cause of hemorrhage.…”
Section: Discussionsupporting
confidence: 55%
“…Zinc deficiency is thought to be responsible for poor wound healing (Medicine 2003). As for magnesium the content ranged from 9.19 ppm to 18.6 ppm was lower than 300 ppm recommended daily as confirm Yu et al 2020 [31], its deficiency contributes to the aging of the skin, which can lead to a skin healing disorder, as supported by Colboc and Meaume 2018 [32]. As for calcium, it is essential for the vascular phase of healing leading to hemostasis, coagulation and fibrosis as mentioned by Démarchez 2014 [33], calcium deficiency can be the cause of hemorrhage.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, plasma magnesium level was independently and positively associated with telomere length even after adjusting for covariates. The majority of previous reports suggest that magnesium might have a protective effect on telomere attrition rate [ 32 , 33 , 34 ] whereas O’Callaghan et al [ 35 ] reported a negative association. It has also been reported that primary fibroblasts grown in a magnesium-deficient medium have increased telomere shortening and lose their replicative potential with accelerated expression of senescence-associated biomarkers [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mazidi et al ( 24 ) used data from NHAENS 1999–2001 and found mean (adjusted for sex, age, and race) dietary intakes of magnesium monotonically increased across TL quarters. Yu et al ( 32 ) conducted a cross-sectional study of 467 participants with a mean magnesium intake of 247.13 mg/day and found an inverse relationship between dietary magnesium and LTL. O’Callaghan et al ( 33 ) used data from 23 South Australians aged 65 years or older and found a negative association between telomere length and serum magnesium levels ( r = −0.61, P = 0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%